TINGGALAN ARKEOLOGI MASA HINDU-BUDDHA DI LASEM: SEBUAH KAJIAN FILOARKEOLOGI - Wijaya, Candrika Ilham; Wirasanti, Niken (Handep: Jurnal Sejarah dan Budaya, 2024)
During the Hindu-Buddhist period, Lasem became a vassal of Majapahit led by a queen named Bhre Lasem. Lasem was historically significant during the Majapahit period. However, complete archaeological data from the Hindu-Buddhist era is unavailable due to the extensive destruction of sacred buildings, particularly temples, caused by the Dutch East India Company (VOC) and the Regent Suroadimenggolo after the Lasem War. This study aims to conduct an inventory of the classical sites in Lasem and to gain insight into the significance of sacred buildings during that period. The study employed philloarchaeological analysis, comparing the textual data from Babad Lasem, Rapporten Oudheidkundigen Diens (ROD), and field surveys. The results indicate that the designation of the sacred building is in line with Nāgarakŗtāgama’s description of the functions of saiwa, sogata, and rsi. Furthermore, its location complies with the principles of caturāśrama and the concept of the triloka—the sacred building of worship, the holy building of hermitage, and the sacred building of dharma (dharmaan). The temple in Lasem represents the harmony of the macrocosm and microcosm, functioning as a relation between sacred buildings serving as examples of applying the concept of the triloka (three realms). This study underscores the interdependence of sacred buildings, representing the manifestations of the three realms